Factors that influence the criminal justice response to human trafficking: a systematic review of North American and European studies - Cooper, Fallon Isabella (Crime, law and social change, 2024)
Human trafficking, the recruitment and transportation of persons by use of force, coercion, or deception for exploitation is one of the largest illicit industries worldwide. In the execution of anti-trafficking policies to combat this phenomenon, nation-states have assigned a decisive role to criminal justice actors as they are not only responsible for the detection, investigation, and prosecution of perpetrators but also for the identification and (legal) protection of victims of human trafficking. However, research has shown that criminal justice actors encounter many challenges whilst carrying out their tasks, which is also reflected in the low numbers of successful prosecutions and identified victims. To our knowledge, the reasons behind this observation have never been studied systematically. This systematic review aims to collect and synthesise empirical literature on factors that influence the criminal justice response to human trafficking to better understand and identify gaps in knowledge. In total, 35 empirical studies were included. Findings were discussed in light of theory and previous research and were used to provide recommendations for policy and future research. These studies suggest that factors such as prevailing stereotypes, an absence of legal guidance and a lack of capacity and expertise interact and even amplify each other and that strengthening the criminal justice response to human trafficking requires a multi-layered approach that simultaneously addresses several challenges.